Novel Trajectories of Bromocriptine Antidiabetic Action: Leptin-IL-6/ JAK2/p-STAT3/SOCS3, p-IR/p-AKT/GLUT4, PPAR-γ/Adiponectin, Nrf2/PARP-1, and GLP-1 - Reda, Enji; Hassaneen, Sherifa; El-Abhar, Hanan S. (Frontiers in Pharmacology, 2018)
Abstract Bromocriptine (BC), a sympatholytic dopaminergic D2 receptor agonist, has been comprehensively used in clinic to treat Parkinson's disease (PD) and prolactinomas. Besides, BC represents a novel therapeutic option in type 2 diabetes (T2DM); however, the precise mechanisms are not completely unveiled. Hence, the objective of the current work is to clarify the potential molecular pathways of the insulin sensitizing effect of BC in the skeletal muscle of diabetic rats and to evaluate its possible interaction with sitagliptin (SG) as an add-on therapy. Here experimental model impersonates unhealthy dietary habit and T2DM was adopted, in which rats were fed high caloric diet of fat and fructose for 6 weeks followed by a single sub-diabetogenic dose of streptozotocin (STZ) (35 mg/kg) (HF/Fr/STZ). Diabetic rats were treated with BC, SG at two dose levels (SG10 and SG20) and combination of BC + SG10 for 2 weeks. BC successfully corrected glucose/lipid profile, as well as leptin and GLP-1. On the muscular molecular level, BC curtailed the inflammatory signal IL-6/JAK2/p-STAT3/SOCS3, while enhanced the PPARγ/adiponectin signaling, resulting in activation of the insulin signaling pathway (p-IR/p-AKT/GLUT4).Moreover, BC confirmed its antioxidant capabilities by altering Nrf2 and PARP-1; the study also highlighted novel mechanisms for SG as well. On almost all tested parameters/pathways, the combination regimen surpassed each drug alone to reach a comparable level to the high dose of SG. In conclusion, our finding shed some light on novel antidiabetic mechanisms of BC. The study also points to the potential use of BC as an adds-on to standard antidiabetic therapies.